Effects of Anthopleurin-Q on the Intracellular Free Ca2+ Concentration in Cultured Rat Cortical Neurons - Liu, J.; Wang, F.; Wu, D.; Wang, Y.; Deng, A. (Drug Research, 2014)
The present study was designed to investigate the mechanism underlying the intracellular free Ca2+ concentration ([Ca2+]i) modulated by Anthopleurin-Q (AP-Q), a sea anemone toxin, using whole-cell patch clamp and fluorescence digital imaging techniques. Results indicated that the overall Ca2+ concentration could be augmented in presence of AP-Q. The increase of [Ca2+]i induced by AP-Q was eliminated in Na+-free solution, Ca2+-free solution or in presence of TTX. However, the Ca2+ increase induced by AP-Q could not be influenced by cyclopiazonic acid (CPA), a specific inhibitor of the endoplasmic reticulum Ca2+-ATPase pump. We furthermore demonstrated that voltage-gated calcium channels (VGCCs) blocker verapamil, or inhibitor of the reverse operation Na+-Ca2+ exchanger NiCl2 attenuated AP-Q-induced [Ca2+]i elevation. Furthermore, the inactivation process of Na+ current (INa) was significantly delayed with slightly change of its amplitude by AP-Q. These findings demonstrated that neuron voltage-gated Na+ channels are also targets of AP-Q. Overall, the present results suggested that AP-Q induced calcium influx via Na+-dependent activation of voltage-gated sodium channels (VGSCs), VGCCs and reverse operation of the Na+/Ca2+exchanger.
Keywords: anthopleurin-Q; patch clamp technique; cultured cortical neuron; sodium current